2010
DOI: 10.1021/jp910903s
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effect on the Aggregation Behavior of 1-Decyl-3-methylimidazolium Bromide in Aqueous Solutions

Abstract: Understanding of the specific salt effect on the aggregation behavior of ionic liquids (ILs) is relevant to multiple applications. In this work, the influence of a series of 15 salts on the aggregation behavior of [C(10)mim]Br in aqueous solutions has been investigated by conductivity, fluorescence, and dynamic light scattering. It was shown that NaCl, NaBr, NaI, CH(3)CO(2)Na, NaSCN, NaNO(3), NaBrO(3), NaClO(3), C(6)H(5)COONa, Na(2)CO(3), Na(2)SO(4), Na(2)C(4)H(4)O(6), and Na(3)CH(5)O(7) have salting-out effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 41 publications
5
59
0
1
Order By: Relevance
“…However, temperature, pH, and low salt concentration have a slight effect. This behavior is similar to that of some zwitterionic surfactants, such as C 12 H 25-N(CH 3 ) 2 CH 2 COO À [43] and dioctanoylphosphatidylcholine (diC 8 PC) [64], but is different from that of cationic SAILs, such as [C n mim]Br [20,41]. This demonstrates the surface adsorption and micelle behavior of the zwitterionic SAILs are analogous to traditional zwitterionic surfactants rather than cationic SAILs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, temperature, pH, and low salt concentration have a slight effect. This behavior is similar to that of some zwitterionic surfactants, such as C 12 H 25-N(CH 3 ) 2 CH 2 COO À [43] and dioctanoylphosphatidylcholine (diC 8 PC) [64], but is different from that of cationic SAILs, such as [C n mim]Br [20,41]. This demonstrates the surface adsorption and micelle behavior of the zwitterionic SAILs are analogous to traditional zwitterionic surfactants rather than cationic SAILs.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous SAILs based on imidazolium, pyridinium, pyrrolidinium cations with different hydrocarbon chain lengths were studied extensively using a variety of methods, such as surface tension, 1 HNMR, steady-state fluorescence spectroscopy, and conductivity measurements [10][11][12][13][14]. Additionally, the effects of anionic nature (e.g., Cl À , Br À , NO À 3 , I À , BF À 4 , CF 3 SO À 3 , CH 3 COO À , ClO À 4 ) [15][16][17][18], various organic additives [19], and salts [20] on the aggregation behavior of SAILs in aqueous solutions were investigated. All the above studies indicate that we can control the aggregation behavior of SAILs in aqueous solutions by altering the alkyl chain length, cationic ring structure, and anionic type, as well as organic additives and salts.…”
Section: Introductionmentioning
confidence: 99%
“…Reports has shown that [2,31] counter-ions with large size bind more effectively to micelle surface which promote decrease in electrostatic repulsion between the head groups of surfactant, thereby increase surfactant aggregational tendency resulting into depression of its CMC value. Addition of salt to aqueous media of HTABr lead to the partial reduction of the water of hydrophobic hydration around the alkyl chain of the non-associated surfactant monomers which decreased the energy required to break down this structure during micellization process [18].…”
Section: Fig-2 Schematic Representation Of Counterions At the Stern mentioning
confidence: 99%
“…The modification of interfacial activity and aggregate size/ morphology are crucial for their optimum performance. Such modifications can be achieved by modifying surfactants' own structure [71][72][73] or mixing them with each other [63,64,[74][75][76][77] as well as with additives like salts and different organic compounds [21,[43][44][45][46][47][78][79][80][81]. Considering the need to control aggregate size, vital for various applications, we attempted to investigate the mixed micellization between [bmim] [DS] and Brij30 in presence of two different ions (Na + and NH 4 + ) using dynamic light scattering (DLS), small angle neutron scattering (SANS) and Rheological measurements.…”
Section: Introductionmentioning
confidence: 99%